2020
DOI: 10.1109/access.2020.3004856
|View full text |Cite
|
Sign up to set email alerts
|

A Prediction Model for Bus Arrival Time at Bus Stop Considering Signal Control and Surrounding Traffic Flow

Abstract: The arrival time of bus at the stop is critical data in design of bus operational strategies. Especially for real-time control strategies (i.e., signal priority system), bus arrival time is usually predicted to assess the next bus operation condition in the future (i.e., bus bunching and reliability of transit service) and then can be used as a decision basis of current control actions. The signalized intersection and surrounding traffic are the key factors in bus travel time prediction, but most previous appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The regression analysis method is to analyze the relationship between multiple variables and establish a mathematical function formed by independent variables. According to the linear speed change shown by the relationship between bus speed and traffic density, Zhang et al proposed a bus arrival time prediction model considering upstream signalized intersection and surrounding traffic flow [3]. Zhou et al used the Kalman Filter algorithm to establish a prediction model of bus travel time [4].…”
Section: Statistical Prediction Methodmentioning
confidence: 99%
“…The regression analysis method is to analyze the relationship between multiple variables and establish a mathematical function formed by independent variables. According to the linear speed change shown by the relationship between bus speed and traffic density, Zhang et al proposed a bus arrival time prediction model considering upstream signalized intersection and surrounding traffic flow [3]. Zhou et al used the Kalman Filter algorithm to establish a prediction model of bus travel time [4].…”
Section: Statistical Prediction Methodmentioning
confidence: 99%
“…According to Zhang et al [5] bus arrival time is commonly forecasted to assess future bus operation conditions (e.g., bus bunching and transit service reliability) and can then be used to inform present control actions, particularly for real-time control systems. The time of travel and traffic scenario are the most important components in forecasting, yet most previous techniques have only looked at the impact of signal control on delay in travel time.…”
Section: Related Workmentioning
confidence: 99%
“…The proposed model was tested on two signalized intersections, and it was found that the proposed model outperformed existing models in the literature. Zhang, et al [28] proposed a prediction model for bus arrival time considering signalized control and surrounding traffic flow. The authors adopted the speed-flow-density relationship to derive the travel speed.…”
Section: ) Bus Speed/travel Time Predictionmentioning
confidence: 99%